ANALISIS PSIKOLOGI TOKOH UTAMA DALAM FILM PINTU-PINTU SURGA KARYA ADIS KAYL YURAHMAN - Amelia; Suhardi; Dody Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the psychological analysis of the main character in the film "The Doors of Heaven" by Adis Kayl Yurahmah. The purpose of this study is to analyze the id in the psychology of the main character in the film "The Doors of Heaven" by Adis Kayl Yurahmah, to analyze the ego in the psychology of the main character in the film "The Doors of Heaven" by Adis Kayl Yurahmah, and to analyze the superego in the psychology of the main character in the film "The Doors of Heaven" by Adis Kayl Yurahmah. This research is qualitative using descriptive methods. The instrument used is the researcher herself and is supported by an analysis guide table that helps the researcher to summarize the data obtained. The data in this study are in the form of dialogue excerpts or sentences from the Psychological Analysis of the Main Character in the Film Pintu-Pintu Surga by Adis Kayl Yurahmah. The data collection technique used to obtain research data uses the technique of listening and taking notes. In this study, the researcher uses qualitative analysis techniques which mean data processing techniques used to understand complex phenomena. The steps in analyzing data are presenting the data to be analyzed, grouping data based on psychoanalytic theory through id, ego and superego. Based on the psychological analysis of the main character Latifah in the film Pintu-Pintu Surga by Adis Kayl Yurahmah using Sigmund Freud's theory, Latifah experiences clear personality changes: initially dominated by the Id with spontaneous emotional impulses such as being easily angered, selfish, and acting impulsively; then the Ego appears through self-control, rational thinking, acceptance of advice, and adaptation; until finally the Superego dominates with guilt, regret, prayer, apology, and commitment to morals, social norms, and religious values depicting the inner journey from an emotional person to a mature and moral one.